2017
DOI: 10.1111/cge.13060
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic application of a capture based NGS test for the concurrent detection of variants in sequence and copy number as well as LOH

Abstract: Whole exome sequencing (WES) has made the identification of causative SNVs/InDels associated with rare Mendelian conditions increasingly accessible. Incorporation of softwares allowing CNVs detection into the WES bioinformatics pipelines may increase the diagnostic yield.However, no standard protocols for this analysis are so far available and CNVs in non-coding regions are totally missed by WES, in spite of their possible role in the regulation of the flanking genes expression. So, in a number of cases the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Case 25 (class A, Online Resource 2: Figure S9). The karyotype of this female child (case 8 in Vetro et al 2018), affected by severe neurodevelopmental delay, showed a simple unbalanced translocation der(2)t(2;14)(q37.2;q24.3) in 80% of peripheral blood cells and an apparently normal karyotype in the remaining ones. Array CGH and subtelomeric FISH analysis performed in both blood and fibroblasts revealed a terminal 2q deletion in 100% of the cells, while the 14q duplication was detected in about 70% of blood cells and 30% of fibroblasts.…”
Section: Chromosome Mosaicismmentioning
confidence: 87%
“…Case 25 (class A, Online Resource 2: Figure S9). The karyotype of this female child (case 8 in Vetro et al 2018), affected by severe neurodevelopmental delay, showed a simple unbalanced translocation der(2)t(2;14)(q37.2;q24.3) in 80% of peripheral blood cells and an apparently normal karyotype in the remaining ones. Array CGH and subtelomeric FISH analysis performed in both blood and fibroblasts revealed a terminal 2q deletion in 100% of the cells, while the 14q duplication was detected in about 70% of blood cells and 30% of fibroblasts.…”
Section: Chromosome Mosaicismmentioning
confidence: 87%
“…Furthermore, several studies are ongoing in order to evaluate the benefits that are provided by this technology in routine diagnostics, above all in ovarian cancer BRCA1/2 assessment [ 13 , 14 , 15 , 16 , 17 ]. NGS platforms are able to provide reliable qualitative data: nevertheless, one of the main challenges regards its ability to precisely identify quantitative changes, like gain or loss in the genes investigated [ 18 , 19 ]. Allele status evaluation is becoming a powerful marker of genome instability, being one of the defected targeted by PARP-1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…To test for any possible constitutional or mosaic mutation that could explain the polymicrogyria, proband’s DNA from both blood and saliva was analysed by OneSeq protocol, at an average coverage of 194.3x and 134.7x, respectively, on an Illumina HiSeq2500, as previously described. 15 After reads alignment, variant calling, annotation and filtering for possible artefacts was done as previously reported. 16 …”
Section: Molecular Studiesmentioning
confidence: 99%